Isolation of Alpaca Anti-Hapten Heavy Chain Single Domain Antibodies for Development of Sensitive Immunoassay - Kim, Hee-Joo (2011)
Some unique subclasses of Camelidae antibodies are devoid of light chain and the antigen binding site is comprised exclusively of the variable domain of the heavy chain (VHH). Although conventional antibodies dominate current assay development, recombinant VHHs have a high potential as alternative reagents for the next generation of immunoassay. We expressed VHHs from an immunized alpaca and developed a VHH-based immunoassay using 3-phenoxybenzoic acid (3-PBA), a major metabolite of pyrethroid insecticides as a model system. A phage VHH library was constructed and seven VHH clones were selected by competitive binding with 3-PBA. The best immunoassay developed with one of these VHHs showed an IC(50) of 1.4 ng/mL (limit of detection (LOD) = 0.1 ng/mL). These parameters were further improved by using the phage borne VHH, IC(50) = 0.1 ng/mL and LOD = 0.01 ng/mL. Both assays showed a similar tolerance to methanol and dimethylsulfoxide up to 50% in assay buffer. The assay was highly specific to 3-PBA and its 4-hydroxylated derivative, 4-hydroxy 3-PBA (150% cross reactivity) with negligible cross reactivity with other tested structural analogs and the recovery from spiked urine sample ranged from 80 to 112%. In conclusion, a highly specific and sensitive VHH for 3-PBA was developed using sequences from immunized alpaca and phage display technology for antibody selection.